Expressões metafóricas e o instagram : uma proposta de leitura e ampliação de sentidos em língua portuguesa para alunos surdos - Santos, Luana da Mota (2020)
The deaf to have broad access to knowledge must share the writing of the listening world. Thus, the reading of different textual genres and their multimodality is essential for learning to write Portuguese, as well as for understanding the social, cultural and ideological context that has passed. Our main motivation is precisely this construction of meaning performed by deaf people when interpreting texts rich in metaphorical expressions. In this context, the interpretation attributed to texts by the deaf sounds strange to many listeners and this is due to cultural traits and linguistic differences. Based on these observations, the main objective of this Final Conclusion Work (TCF) of the Professional Master of Arts (PROFLETRAS) is to contribute to a reflection on the teaching of Portuguese language to the deaf as a second language (L2), presenting an intervention practice directed to three students in the resource room of a state school located in the municipality of Itabaiana / SE. In addition to the description of the bases theoretical-methodological, the results of the effective application will be presented and a final product consisting of the creation of an educational page on Instagram, a social network with more than one billion users used to share photos and videos and which will serve to publicize the activities developed . The chosen textual genre was the advertisement, since in it we find, among other linguistic resources, conceptual metaphors, and consequently idiomatic expressions (IS). For this, the theoretical basis that underlies this position is based on the studies of Lakoff and Johnson (1980, 2002), with the principle of projection of ownership of the Theory of Conceptual Metaphor. The conceptions of textual genre and reading were supported, fundamentally, in Marcuschi (2005, 2008). The criteria that define the analysis of the IS are found in Ortíz Alvarez (2000). In addition, as it is an intervention to solve a diagnosed problem, the methodology adopted in this work uses some elements of action research by Thiollent (2011). Rojo (2012, 2015) prove that new technologies require the development of different skills for understanding hypertexts, so they also form the theoretical basis of this work, together with Farias (2002, 2003, 2006) and Costa (2015), among others, who approach the universe of deafness and the teaching of Portuguese as L2. The results of this research showed that differentiated teaching strategies, supported by academic studies and developed by teachers in the classroom, promote a broader understanding of LP by deaf bilingual students. In addition, the use of different semioses, as well as the advertising genre, facilitated the critical literacy of all involved from the work of reading and understanding the IS, thus contributing to the expansion of the reading of the world of these students.